Assessment of Some Potentially Toxic Inorganic Contaminants in Soil of the Obi Coalfield, Middle Benue Trough, Nigeria - Adamu M.S , Mangs A.D , Lar U.A, Sallau, A.K, (International Journal of Scientific Research and Management (IJSRM), 2015)
:The study area has occurrences of coal, limestone and sulphide minerals, with ubiquitous artisanal mining activities. This research assesses heavy metal accumulation in soil of the area, using pollution indices such as geo-accumulation index (Igeo), enrichment factor (EF), contamination factor (CF) and pollution load index (PLI). A total of 13 soil samples were analyzed for As, Ba, Co, Cr, Cu, Mo, Ni, Pb, Sc, Sr and Zn, using ICP-OES geochemical technique. Results show that soil in the area are extremely polluted by Ni, Cr and Zn, having Igeo values of 5.88, 3.56 and 2.43 respectively, going by geo-accumulation index. Igeo levels of Pb, Cr and Ba indicate moderate to no pollution. Enrichment factor analysis, again show that Ni and Cr have EF of 147.17 and 79.66 respectively, indicating the two are extremely severely enriched in the environment, while Zn, Co and Sr with EF between 6 and 15, indicate moderate enrichment. Cu, Mo and As levels in soil remain very low, indicating the media are not contaminated by these elements. Most of the locations showed a PLI less than one (1) in the ranking, indicating no serious pollution occurring. The high Igeo and EF values recorded for some heavy metals are related to mining, mineral processing as well as the sub-standard practice dumping of mine wastes and tailings, in addition to natural weathering, releasing these elements into the environment. The nature and source of enrichment of these elements can therefore be said to be anthropogenic. Pathways of exposure of the human population to the heavy metals were found to be through dust inhalation, from the mouth through the ingestion of food and water as well as through the skin, resulting from the close association of the population to the land/soil due to farming and water used for drinking and other domestic uses. These can result to varied human health risks if the population is continually exposed. High doses of Ni and Cr can cause lung, nasal and possible stomach cancer may develop. Also, elements such as Pb and As, are known to be toxic even at very low exposure, also, with carcinogenic effects. It is recommended here that the quality of drinking and irrigation water as well as some crops grown from the area be investigated and quality determined, with regards to the levels of heavy metals in such media, thereby determining whether the population is safe or not. This should include massive awareness campaign for the miners and the mining communities, so as to forestall any negative eventuality.